Understanding health care needs among Veterans with Parkinson's disease: A survey study - Feeney, Megan; Duda, John; Hiller, Amie; Phillips, Jay; Evers, Christiana; Yarab, Nicole; Todaro, Veronica; Rader, Lydia; Rosenfeld, Sheera (Frontiers in Neurology, 2022)
Among Veterans, it is estimated that 110,000 are living with Parkinson’s disease (PD) in the United States. Whether or not Veterans living with PD are enrolled in the Veterans Health Administration (VHA), they may require special considerations when it comes to their care. We administered a survey to Parkinson’s Foundation constituents with PD who had previously reported their Veteran status. Our goal was to identify areas where intervention can lead to improved health outcomes for Veterans living with Parkinson’s disease. We specifically wanted to examine 1) the proportion of our Veteran constituents receiving services through the VHA, 2) the comprehensive care services that were utilized by Veterans living with PD, and 3) self-reported mental health and mobility status. We also wanted to compare those receiving care within and outside the VHA to see where there may be areas for improvement. With a response rate of 29.8% we received surveys from 409 United States Veterans with PD. As expected, mental health (MH) concerns in the previous 12 months were common with 36.0% of Veterans reporting concerns. Only 22.1% of respondents received care through VHA. Respondents with more falls and mental health concerns as well as those with higher levels of education and younger age were more likely to be seen at a VHA facility. In this sample, education level, household income, marital status, and VHA status were positively associated with increased health care utilization among Veterans. Those seen within the VHA were more likely to utilize MH and speech and language pathology consultation. This study highlights the importance of targeting educational outreach about care best practices for Veterans living with PD beyond VHA’s current reach as well as the importance of access to good MH resources.